Strengthening Financial Transparency in U.S. Nonprofits: Reducing Fraud and Mismanagement of Government Funds (International Journal of Scientific Research and Management (IJSRM), 2024)
Financial transparency in U.S. nonprofits is essential to maintaining accountability, preventing fraud, and ensuring the responsible use of government funds. Despite existing regulatory frameworks, financial mismanagement and fraudulent activities continue to pose significant challenges. This article explores the current state of financial transparency in the nonprofit sector, highlighting key challenges, regulatory measures, internal control mechanisms, and emerging technological solutions. By examining real-world cases and best practices, the paper provides actionable recommendations for enhancing financial oversight and reducing fraud. Strengthening transparency can safeguard public trust, improve organizational efficiency, and ensure the effective utilization of public resources.